Perspectives of Indonesian Accountants and Auditors on the Effectiveness of Corporate Governance and It in Preventing Fraud - Joshua John Patrick; Rindang Widuri (Universitas KH. Abdul Chalim Mojokerto, 2026)
Purpose This study explores the perspectives of accountants and auditors in Indonesia regarding Corporate Governance (CG) and Information Technology (IT). It aims to provide valuable insights for researchers, senior management, and boards of directors on effective fraud prevention strategies. Furthermore, the study seeks to enhance awareness of the importance of effective oversight, ethical behavior, and strong corporate governance practices in mitigating corporate failure. Design/methodology/approach. This study employs a survey method involving financial accountants as well as internal and external auditors. A one-sample test is used to evaluate the significance of Corporate Governance in fraud prevention. Paired sample tests are applied to compare traditional audit techniques with IT-based methods, while one-way ANOVA is conducted to assess differences in perspectives among respondents. Findings The results indicate that Corporate Governance has a significant impact on fraud prevention, with internal audit departments identified as the most utilized CG mechanism. Additionally, Information Technology demonstrates a comparable impact to traditional fraud prevention methods. Internal control reviews and improvements are the most frequently employed traditional techniques, whereas continuous auditing emerges as the most widely used IT-based approach for fraud prevention. Research implications/limitations The findings emphasize that strong corporate governance is essential for effective fraud prevention, requiring organizations to continuously enhance their governance practices. The integration of IT tools with traditional fraud prevention methods is recommended to develop a more comprehensive and effective strategy.Originality/value This study contributes to the existing literature by examining the role of Corporate Governance and Information Technology in fraud prevention and detection, particularly within Southeast Asia and other emerging economies. It offers important insights for both academics and practitioners in Indonesia, as well as for the international community.